2016
DOI: 10.5539/ijel.v6n7p166
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Typology

Abstract: An abstract is a brief and comprehensive summary of the contents of the article. It allows readers to survey the various definitions that have been presented by scholars about the concept of curriculum as a "plan" or "product", and due to the vast variation of definitions, many classifications have been made in regarding them. Since "the curriculum" is not a "type" but has "types" itself, it is not possible to present a comprehensive definition for all those curricula such as intended, implemented, learned, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Moreover, responding to the environment is the ultimate criterion for preserving the curricula effectiveness. The present study seeks to examine the effectiveness of medical education curriculum owing to the major role of this component in fulfilling the goals and missions of medical education and given that different researchers and experts refer to curriculum as "the heart of medical education system" (2) or as a teaching/learning map and present comprehensive definitions for curriculum as a science (15). Focusing on this component definitely leads to fulfilling the goals and missions of medical education, i.e.…”
mentioning
confidence: 99%
“…Moreover, responding to the environment is the ultimate criterion for preserving the curricula effectiveness. The present study seeks to examine the effectiveness of medical education curriculum owing to the major role of this component in fulfilling the goals and missions of medical education and given that different researchers and experts refer to curriculum as "the heart of medical education system" (2) or as a teaching/learning map and present comprehensive definitions for curriculum as a science (15). Focusing on this component definitely leads to fulfilling the goals and missions of medical education, i.e.…”
mentioning
confidence: 99%
“…Similarly, the findings are in agreement with Makunja (2016) who suggested most teachers in Tanzania had limited knowledge on assessment and evaluation while implementing a new curriculum. Marzooghi (2016) conducted a study to identify how students view a new curriculum. It was revealed that the students were taking it for granted especially since there were no frequent assessments which is in agreement with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…When looking at the various definitions of the curriculum in the literature, it is possible to see that the concept of curriculum has been handled as what is taught in schools, a subject area, content, a set of materials, everything planned by the school, and a set of experiences gained by students in a school (Marzooghi, 2016). Although there are curriculum definitions from different perspectives in the literature, it can be easily seen that there has been a constant effort to make a better and single definition.…”
Section: Conceptual Frameworkmentioning
confidence: 99%